ANALISIS YURIDIS PUTUSAN BEBAS DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Mulyo, Joyo (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The discrepancy in the application of the law in accordance with the provisions of the Corruption Crime Eradication Law is the imposition of an acquittal at the Central Jakarta District Court with an issue raised by the Public Prosecutor. The legal provisions regarding gratuities that have been stipulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes juncto Article 64 paragraph (1) of the Criminal Code, because the element of